Single versus multiple hyperthermic intraperitoneal chemotherapy applications for T4 gastric cancer patients: Efficacy and safety profiles - Zhang, Jing; Sun, Yuemin; Bai, Xiaofeng; Wang, Peng; Tian, Liang; Tian, Yantao; Zhong, Yuxin (Frontiers in Oncology, 2023)
Objective: To explore the clinical safety and efficacy of single and multiple applications of lobaplatin-based hyperthermic intraperitoneal chemotherapy (HIPEC) for patients with T4 gastric cancer and to evaluate the impact of HIPEC on peritoneal metastasis. Materials and Methods: We retrospectively reviewed prospectively collected data from T4 gastric cancer patients who underwent radical gastric resection plus HIPEC between March 2018 and August 2020 from the National Cancer Center and Huangxing Cancer Hospital. Patients who underwent radical surgery and HIPEC were divided into two groups: the single-HIPEC group (radical resection + a single application of intraoperative HIPEC with lobaplatin 50 mg/m2 at 43.0 ± 0.5 °C for 60 min), and a multi-HIPEC group (two more HIPEC applications were performed after radical surgery). Results: A total of 78 patients were enrolled in this two-center study; among them, 40 patients were in the single-HIPEC group, and 38 patients were in the multi-HIPEC group. The baseline characteristics were well balanced between the two groups. There was no significant difference in the postoperative complication rates between the two groups (P > 0.05). Mild renal dysfunction, mild liver dysfunction, low platelet levels and low white blood cell levels were recorded in both groups, without significant differences between the two groups (P > 0.05). After a mean follow-up of 36.8 months, 3 (7.5%) patients in the single-HIPEC group and 2 (5.2%) patients in the multi-HIPEC group experienced peritoneal recurrence (P > 0.05). Both groups had comparable 3-year overall survival (OS) (51.3% vs. 54.5%, P = 0.558) and 3-year disease-free survival (DFS) rates (44.1% vs. 45.7%, P = 0.975). Multivariate analysis showed that an age > 60 years and low preoperative albumin levels were independent risk factors for postoperative complications. Conclusion: Single and multiple applications of HIPEC in patients with T4 gastric cancer were safe and feasible. Both groups had similar postoperative complication rates, 3-year OS rates and 3-year DFS rates. Special attention should be given to HIPEC for patients aged > 60 years and patients with low preoperative albumin levels.